ANALISA RANGKA BATANG 2D MENGGUNAKAN METODE MATRIKS KEKAKUAN STRUKTUR DAN SAP 2000 - Christiani Chandra Manubulu; Merzy Mooy; Igidro Sampaio Soares Serra (Program Studi Teknik Sipil Universitas Katolik Widya Mandira, 2022)
understanding of stiffness is primarily done by using simple structural examples. The size of the structure in calculations is always represented by the large number of linkage and the element of the rod so that the use of the computer and the application of the accounting must correspond to the modeled structure model. One of the popular applications used in performing structural calculations is ms excel. The goal for the study is to create an alternative ms-oriented structural analysis aid and to make comparisons of calculation with other output applications already on the market. Excel - oriented stiffness calculation makes a tabbing of analysis of which the physical form of Numbers can be clearly displayed and that can be examined at a theoretical level of analysis. The transparent process of accounting increases trust in the results so that it can be used in education and as a comparison to the output of other applications. The calculating two-dimensional skeletal structure with alternative aid programs and the SAP 2000 application program, provides a very small difference so that it can be deduced that an alternative assistive program output can be used.